Hygiene Awareness Among Fuchka Vendors and Consumers in Bangladesh: A Study on Social Determinants of Health - Hossain, Abul; Habib, Ahsan (Technium Social Sciences Journal, 2023)
The article, "Hygiene Awareness Among Fuchka Vendors and Consumers in Bangladesh: A Study on Social Determinants of Health," delves into the intricate relationships between social determinants of health (SDH) and hygiene practices in the context of street food culture in Bangladesh, with a particular emphasis on the popular snack, Fuchka. Drawing from extensive fieldwork, including focus group discussions with consumers and in-depth interviews with Fuchka vendors, the study seeks to understand the health implications of Fuchka consumption, the reasons behind its widespread appeal, and the lived experiences of both vendors and consumers. Results reveal a substantial impact of factors like income, education, occupation, and gender norms on hygiene awareness and practices. This is particularly evident when assessing the quality and safety of street foods, with issues like lack of sanitation, use of contaminated water, and exposure to environmental contaminants coming to the fore. The study also highlights the varied experiences of consuming Fuchka across socio-economic strata, emphasizing the disparities in hygiene standards between upscale restaurants and street vendors. Moreover, the paper underscores the critical role of city corporations in regulating street food vending and the urgent need for comprehensive policies that address these SDH to improve public health. Through this lens, the article provides a holistic understanding of the interplay between social determinants, hygiene practices, and health outcomes in the vibrant street food scene of Bangladesh.